High intensity click statistics from a 10 × 10 avalanche photodiode array. (23rd October 2017) - Kröger, Johannes; Ahrens, Thomas; Sperling, Jan; Vogel, Werner; Stolz, Heinrich; Hage, Boris
Abstract: Photon-number measurements are a fundamental technique for the discrimination and characterization of quantum states of light. Beyond the abilities of state-of-the-art devices, we present measurements with an array of 100 avalanche photodiodes exposed to photon-numbers ranging from well below to significantly above one photon per diode. Despite each single diode only discriminating between zero and non-zero photon-numbers we were able to extract a second order moment, which acts as a nonclassicality indicator. We demonstrate a vast enhancement of the applicable intensity range by two orders of magnitude relative to the standard application of such devices. It turns out that the probabilistic mapping of arbitrary photon-numbers on a finite number of registered clicks is not per se a disadvantage compared with true photon counters. Such detector arrays can bridge the gap between single-photon and linear detection, by investigation of the click statistics, without the necessity of photon statistics reconstruction.